Bolivia : Staff Report for the 2001 Article IV Consultation and Request for Third Annual Arrangement Under the Poverty Reduction and Growth Facility. (IMF Staff Country Reports; Country Report ;, 2001)
Bolivia has a long track record of substantial progress in the areas of macroeconomic stability and structural adjustment; however, poverty remains widespread. Although there were significant delays and setbacks in the execution of the structural adjustment program, some important advances were achieved, mainly in the areas of tax administration and budget management. The Bolivian authorities have developed a comprehensive poverty reduction strategy. The government's medium-term economic program is designed to raise growth to 5 percent. Bolivia maintains an open exchange and trade system.